The Effect of Potato Peels and Ascorbic Acid on The Internal Organs of Poultry - Asem Ramadan Amar Mohamed; Abdul hakim Khalefah Alour; Farag Elmhdi Jabreil; Musab Salim Aboulqassim Madi (African Journal of Advanced Pure and Applied Sciences, 2024)
This work was carried out at the Faculty of Veterinary Medicine and Agriculture, University of Zawia, in April 2023, to compare the beneficial effects of dietary potato peels and vitamin C supplementation on the internal organs of poultry. The investigation was conducted on 75 one-day-old broilers, and the birds were divided into five groups of fifteen chicks each. The first group was the control group and fed on a normal diet, the second group was fed on a diet with ascorbic acid 200 mg/kg. The potato peels were added to the diets of the third group at 50 mg/kg, the fourth group at 100 mg/kg, and the fifth group at 200 mg/kg, respectively. The results showed no significant differences in live body weight or the weight after cavitation. The spleen, the gizzard, and the pancreas weight showed no significant differences between the treatments at p < 0.05. The weight of the liver, the heart, and the kidney, there were significant differences between the different treatments compared to the control group, the group fed with pp 100mg/kg recorded a slight difference at the heart level compared to the other treatments at the level p<0.05 2.095a, while the treatment fed with pp 200mg/kg recorded a significant difference at the kidney level, 1.811a compared to the control group. The weight and length of the intestine, and the cecum results showed no significant differences between the treatments.